The economic evaluation of projects : Papers from a curriculum development workshop / David G. Davies - Davies, David G.
This book presents a simplified approach to project evaluation which the Bank is adopting, including how project evaluation should be modified to take into account current economic situations in most countries. The volume highlights issues that arise in applying this methodology and how to resolve them. The two chapters that discuss approaches to teaching economic analysis will be of interest to educators and trainers.